Development of Novel Oral Delivery Systems Using Additive Manufacturing Technologies to Overcome Biopharmaceutical Challenges for Future Targeted Drug Delivery - Micol Cirilli; Julius Krause; Andrea Gazzaniga; Werner Weitschies; Matteo Cerea; Christoph Rosenbaum (Pharmaceutics)
Background/Objectives: The development of targeted drug delivery systems for active pharmaceutical ingredients with narrow absorption windows is crucial for improving their bioavailability. This study proposes a novel 3D-printed expandable drug delivery system designed to precisely administer drugs to the upper small intestine, where absorption is most efficient. The aim was to design, prototype, and evaluate the system’s functionality for organ retention and targeted drug release. Methods: The system was created using 3D printing technologies, specifically FDM and SLA, with materials such as PLA and HPMC. The device was composed of matrices and springs, with different spring geometries (diameter, coil number, and cross-sectional shape) being tested for strength and flexibility. A gastro-resistant string was used to maintain the device in a compact configuration until it reached the neutral pH environment of the small intestine, where the string dissolved. The mechanical performance of the springs was evaluated using a texture analyzer, and the ability of the system to expand upon pH change was tested in simulated gastrointestinal conditions. Results: The results demonstrated that the system remained in the space-saving configuration for two hours under acidic conditions. Upon a pH change to 6.8, the system expanded as expected, with opening times of 5.5 ± 1.2 min for smaller springs and 2.5 ± 0.3 min for larger springs. The device was able to regain its expanded state, suggesting its potential for controlled drug release in the small intestine. Conclusions: This prototype represents a promising approach for targeted drug delivery to the upper small intestine, offering a potential alternative for drugs with narrow absorption windows. While the results are promising, further in vivo studies are necessary to assess the system’s clinical potential and mechanical stability in real gastrointestinal conditions.